Content analysis of gay and lesbian Filipiniana books of the University of the Philippines Diliman library collection - Trinidad, Deoji O.; Cabbab, Johann Frederick A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2011)
The University of the Philippines Library collection has a substantial number of Filipiniana print materials about gays and lesbians. This study use content analysis to analyze the materials' discussion of the eight gay and lesbian issues of self-identity, stereotypes, violence, discrimination, religion, family and relationships, health, and education and career.
The most prevalent gay and lesbian issues on the materials are self-identity, discrimination, and family and relationships being present in all of the 22 materials analyzed. The issues of education and career, stereotype, and violence come in second with 95.5% while religion (90.1%) and health (86.4%) are the third and fourth prevalent issues, respectively.
Out of the 22 gay and lesbian Filipiniana materials, only 17 have a complete discussion on the issues while 4 materials have 87.5%(7 out of 8 issues) on the total percentage of discussions. One material has a 50% (4 out of 8 issues) rating on the completeness of discussions of the issues.
The presence of the issues in the materials analyzed confirms the hypothesis that the current collection offers enough relevant information to the gay and lesbian population. The 88% rating of the balanced treatment of the issues also shows that the collection, however small in quantity, presents the users a balanced discussion on the available material.
Vita.
Thesis (Bachelor of Library and Information Science)
Undergraduate thesis (B.L.I.S.)--University of the Philippines, Diliman.
Keywords: Content analysis(Communication).; Sex role in literature